ANALISIS PENCEMARAN LIMBAH MIKROPLASTIK PADA BEBERAPA JENIS IKAN DI MUARA SUNGAI KENYAMUKAN SANGATTA, KABUPATEN KUTAI TIMUR - Alfiyyah Rifda Saputri; Sri Purwati; Makrina Tindangen; Sonja Verra Tinneke Lumowa (Bioedukasi Jurnal Pendidikan Biologi, 2025)
Microplastics are plastic particles smaller than 5 mm that originate from anthropogenic activities or environmental degradation. The estuarine waters of the Kenyamukan River in Sangatta, East Kutai Regency, are highly vulnerable to microplastic contamination due to intensive local activities such as fishing port operations, residential settlements, docks, and tourism sites. This study aimed to analyze the types and forms of microplastics found in several fish species inhabiting the estuarine area. The research employed a descriptive–analytical approach, with sampling conducted from March to May 2025. Fish organs analyzed included the gills and digestive system, which were extracted using NaCl solution, 10% KOH, and 30% Hâ‚‚Oâ‚‚, followed by observation under a stereo microscope. The results revealed the presence of microplastics in goatfish (Parupeneus indicus), spotted scat (Scatophagus sp.), rabbitfish (Siganus guttatus), and golden snapper (Lutjanus johnii). The identified microplastic types consisted of fibers (52%), fragments (27%), films (12%), and pellets (9%), with a total of 173 particles. The microplastic sizes ranged from 0.0012 mm to 0.1399 mm and exhibited various colors, including black, red, yellow, blue, green, transparent, orange, and pink. These findings indicate a high level of microplastic contamination in the Kenyamukan River estuary, posing potential threats to the aquatic ecosystem and the trophic food chain.